Extinction during memory reconsolidation blocks recovery of fear in adolescents - Johnson, D. C. (Sci Rep, 2015)
Adolescence is a time of intensified emotional experiences, during which anxiety and stress-related disorders peak. The most effective behavioral therapies for treating these disorders share exposure-based techniques as a core component. Exposure-based therapies build on the principles of fear extinction learning and involve desensitizing the individual to cues that trigger anxiety. Yet, recent evidence shows an adolescent-specific diminished capacity to extinguish fear responses, suggesting that adolescents may respond less well to exposure-based therapies than other age groups. Here we demonstrate an alternative method for blocking the recall of fear memories in adolescents, building on principles of memory reconsolidation in adults. During memory reconsolidation, a memory that is recalled becomes labile during which time it can be updated. Prior research has shown that extinction training during memory reconsolidation attenuates the recovery of fear memory in human adults and in rodents. Using this method, we show attenuation of fear memory in adolescent humans. These findings have significant implications for treating one of the most vulnerable populations to anxiety and stress related disorders - adolescents - by optimizing exposure therapy based on principles of memory reconsolidation.